(untitled) (Perioperaciina Medicina, 2018)
The purpose of this article was to systematize available literary data and to provide general recommendations for respiratory therapy in patients with spinal muscular atrophy. Spinal muscular atrophy (SMA) is a severe neuromuscular disease with autosomal recessive inheritance with degeneration of alpha motor neurons in the anterior horns of the spinal cord, leading to progressive proximal muscle weakness and paralysis. SMN 1–2 genes potentially encode identical proteins, although most of the transcripts of the SMN1 genes are halfsized, whereas most transcripts of the SMN2 genes do not contain the seventh exon. Therefore, the SMN2 gene is only partially functional, and a low-level SMN protein is produced in SMA patients. Moreover, the number of copies of the SMN2 can not be considered an exact predictive factor for any particular patient. The main causes of mortality and deterioration in the quality of life are the development of secondary respiratory failure. Type 1 (a, b, c) is the heaviest: early onset and lack of motor abilities, usually patients with a disease of this type survive no more than 2 years. Type 2 – an intermediate type characterized by a later onset, the patient may take a sedentary position, survival may reach the adult height. Type 3 is the softest form that manifests itself at the age of 1 year, the patient can walk and stand. The forecast is more favorable. Type 4 “adult form” manifests itself at the age from 10 to 20 or from 20 to 30 years and has a favorable outlook. The main causes of respiratory failure in patients with neuromuscular diseases are weakness of the respiratory muscles, unproductive cough and sleep disturbances. The weakness of the respiratory muscles, defined as the inability of resting respiratory muscles in the state of rest to create a normal level of pressure and air flow velocity when entering and exhaling, is common. Patients with neuromuscular diseases are susceptible to sleep disruption, especially in the REM sleep phase, with the most frequent form of this disorder being hypoventilation. Over time, hypoventilation in a dream can become more prolonged, resulting in the development of a severe form of hypoxia, an increase in the level of carbon dioxide in the blood and the suppression of the activity of the respiratory center. Thus, as a result of the review of literary data, a strategy of respiratory support in patients with CMA was proposed.